Enantioselective Reductive (Hetero)Arylation of Cyclic N‐Sulfonyl Imines by Cobalt Catalysis. Issue 19 (30th March 2023) - Xiao, Jieshuai; Wang, Minyan; Yin, Xuwen; Yang, Shuo; Gu, Pei; Lv, Xueli; Zhao, Yue; Shi, Zhuangzhi
Abstract: Transition‐metal‐catalyzed enantioselective addition of aryl organometallic reagents to imines has emerged as one of the most powerful tools for the formation of optically active diarylmethylamines. Here, we report the first asymmetric reductive (hetero)arylations of imines using aryl and heteroaryl halides enabled by a chiral cobalt‐bisphosphine catalyst. This approach shows good functional group compatibility and complements the reported strategy without use of organometallic reagents. Mechanistic investigations supported that aryl‐cobalt, instead of an arylzinc reagent, was formed in situ in this reductive aryl‐addition event. Abstract : Asymmetric reductive (hetero)arylations of imines using aryl and heteroaryl halides have been uncovered with a chiral cobalt‐bisphosphine catalyst. This approach complements the traditional strategy using preformed organometallic reagents, and it exhibits good functional group compatibility under mild conditions.